Comparison of antibacterial and antibiofilm activity properties of Hypogymnia tubulosa (Schaer.) Hav. lichen extracts from different locations in Turkey - (:unkn) unknown (Guizhou Key Laboratory of Agricultural Biotechnology, 2017)
The levels of bioactivity in lichens can change in response to environmental stress. For this reason, it was decided to compare the activity levels of Hypogymnia tubulosa (Schaer.) Hav. (Parmeliaceae) samples collected from six different localities in Turkey and the factors that may be effective. We also questioned our opinion that antibacterial activity is not directly proportional to the effectiveness of the antibiotic. The in vitro antibacterial activity and antibiofilm effect of diethyl ether (DE) and chloroform-methanol-acetone (CMA) extracts of the lichen H. tubulosa were explored against two pathogenic microbial strains of Staphylococcus aureus-ATCC 25923 and Enterococcus faecalis-ATCC 29212. Antibacterial activity was screened by disk diffusion method through the minimal inhibitory concentration (MIC). Biofilm inhibitory potency of the extracts was measured by spectrophotometrically. Most of the tested extracts of H. tubulosa demonstrated inhibitory effects against S. aureus and E. faecalis as strong as antibiotics. Differences of the findings depending on locality, habitat and extract variables were evaluated. The most antibacterially active samples were from Bursa (Location 4 and 6), both DE and CMA extracts with MIC values of 100 μg/ml, did not show inhibition effect against the bacterial biofilm. CMA extract of the Bolu sample (Location 3) with lower antibacterial effect, significantly reduced biofilm formation of both strains measured with lower absorbance levels compared to control groups. This result confirms that the samples with low antibacterial activity have more inhibitory effect on biofilm formation. In addition, different results were obtained according to localities among the samples of the same lichen species. Environmental factors influence the active substances produced by lichens. The results of this study present evidences of antibiofilm potential as well as strong antibacterial effect of H. tubulosa as promising source of antibacterial drugs. © Guizhou Academy of Agricultural Sciences.
Keywords: Antibacterial activity; Antibiofilm activity; Hypogymnia tubulosa; MIC